ANALISIS FAKTOR YANG MEMPENGARUHI MINAT AKSEPTOR KB TERHADAP KONTRASEPSI IMPLANT DI PUSKESMAS SUNGAI TABUK 1 - Yunita, Laurensia; Siti Noor Hasanah (Midwifery And Complementary Care, 2023)
Background: Many women experience difficulty in choosing a contraceptive method. This is not only due to the limited options available. One of the advantages of implants is that they are suitable for women who cannot use estrogen-containing drugs, cause lighter bleeding, do not raise blood pressure, and have a lower risk of ectopic pregnancy compared to intrauterine contraceptive devices. Despite its high effectiveness—implant contraception has a failure rate of only 0.2–1 pregnancies per 100 women—it seems to be less favored by the public, particularly among couples of reproductive age. Various factors influence a person's decision in choosing a contraceptive method. These include individual factors such as age, parity, education, and knowledge. Objective: To identify the factors that influence the interest in the implant contraceptive method in the service area of Puskesmas Sungai Tabuk 1. Method: This research used a non-experimental descriptive design with a cross-sectional approach. The sampling technique used was simple random sampling. The study sample consisted of 87 family planning (KB) acceptors in the Puskesmas Sungai Tabuk 1 area. Data analysis was conducted using the chi-square test with a questionnaire as the research instrument. Results: The results showed that 62.1% of the respondents were of a certain age group, 40.2% had low knowledge, 59.8% of respondents with certain parity levels were not interested in implants, and 60.9% had a certain level of education. Statistical tests indicated significant relationships between age (ρ = 0.000), knowledge (ρ = 0.000), parity (ρ = 0.000), and education (ρ = 0.000) with interest in implant contraception. Keywords: Acceptors, Implants, Interest